North-South technology transfer in unionised multinationals - Lommerud, Kjell Erik (2010)
We study how incentives for North-South technology transfers in multinational enterprises are affected by labour market institutions. If workers are collectively organised,incentives for technology transfers are partly governed by firms' desire to curb trade union power. This will affect not only the extent but also the type of technology transfer. While skill upgrading of southern workers benefits these workers at the expense of northern worker welfare, quality upgrading of products produced in the South may harm not only northern but also southern workers. A minimum wage policy to raise the wage levels of southern workers may spur technology transfer, possibly to the extent that the utility of northern workers decline. These conclusions are reached in a setting where a unionised multinational multiproduct firm produces two vertically differentiated products in northern and southern subsidiaries, respectively.